PERSEPSI PENDIDIK TERHADAP INTEGRASI MATERI EKONOMI DIGITAL DALAM PEMBELAJARAN IPS SEKOLAH DASAR - Mitia Sismi; Marinda Siska; Leony; Serpadeni; Sumanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The growth of the digital economy has fundamentally reshaped patterns of consumption, transaction, and economic activity in society, including the younger generation who grow up as digital natives. This phenomenon demands renewal of Social Studies (IPS) learning content in elementary schools so that students gain a foundational understanding of the digital economy from an early age. The success of integrating this content largely depends on teachers' perceptions, since teachers play the central role in designing and implementing classroom instruction. This study aims to describe educators' perceptions of the integration of digital economy material into Social Studies learning in elementary school. The study employed a quantitative descriptive approach involving all eighteen teachers at SDN 76/III Lubuk Nagodang as respondents. Data were collected through a Likert-scale questionnaire measuring four indicators: conceptual understanding, perceived urgency of integration, competence readiness, and availability of learning resources, then analyzed descriptively using percentages and score-interpretation categories. The results show that most teachers hold a positive perception of the importance of integrating digital economy material into Social Studies learning, although the level of digital competence readiness and availability of learning resources remain in the moderately positive category. Teachers considered digital economy material relevant to students' daily lives, yet limited training and technological facilities remain the main obstacles to implementation. This study recommends continuous professional training, provision of contextual digital learning resources, and school-policy support to strengthen the integration of digital economy content within the elementary Social Studies curriculum.